Two new sesquiterpenes from the stems of Tripterygium wilfordii. Issue 5 (4th May 2021) - Xiu, Meng-Xue; Meng, Xiao; Li, Na; Wang, Dong; Xiong, Da-Xi; Jiang, Yi-Yu; Sun, Ya-Nan; Chen, Li; Cui, Long
Abstract: Two new β- dihydroagarofuran-type sesquiterpenes 1 β, 2 α, 6 α, 8 β, 15- pentaacetoxy- 9 α -benzoyloxy- β -dihydroagarofuran (1 ) and 1 β, 2 β, 6 α, 15-tetraacetoxy-9 β -benzoyloxy- β -dihydroagarofuran (2 ), together with five known abietane diterpenoids (3 –7 ) were isolated from ethyl acetate extract of stems of Tripterygium wilfordii . Their structures were elucidated on the basis of detailed spectroscopic and physico-chemical analyses. All the isolates were evaluated for in vitro inhibitory activity against A549, HOS and MCF-7. Among them, compounds 4 and 5 exhibited manifest inhibition on A549, HOS and MCF-7 cancer cell lines.